The effect of income inequality on economic growth: A comparative study between Europe and Latin America - Oppenheim,Fabian (2023)
This bachelor thesis aims to examine the impact of income inequality on economic growth and assess whether the relationship differs between Europe and Latin America. Many studies have been performed to investigate the relationship between inequality and growth, and these have yielded a variation of results. As some research finds income inequality to positively impact growth, while others find the relationship to be negative, this study will explore whether the varying results could depend on regional differences. Most of the prominent papers on the subject were written in the 1990s. However, since the 1990s income inequality within countries has increased across the globe, necessitating the need for a more up to date study. The study employs regression analysis with panel data to empirically investigate the relationship, utilizing a sample of 35 countries spanning the period from 1980 to 2019. To explore regional differences, an interactive variable is incorporated into the analysis to estimate the extent to which the effect of income inequality on economic growth diverges between Europe and Latin America. The findings indicate that income inequality significantly impacts economic growth and that the effect differs between Europe and Latin America. However, it is noteworthy that the signs of the estimated coefficients vary depending on the specific inequality variable employed and whether lagged or non-lagged values of the inequality variable are utilized.
Keywords: Income Inequality; Economic Growth; Gini Coefficient; Panel Data; Latin America; Europe